Gestión de residuos sólidos generados en el proceso de trabajo estudiantil en la FAUA - UPAO - Boggiano-Burga, María Lucía (2023)
During their university years, the student of architecture carries out several hands-on works that are essential for their academic development such as the making of models, plans, and reports that are mostly discharged later without considering their value. Therefore, the aim of this research was to analyze the management of solid waste generated in the FAUA-UPAO Architecture Program, considering the principles of the 5Rs and the recycling culture that students have. For this, the waste produced was sorted out based on its lifetime and toxicity level. Secondly, 218 surveys were applied to students chosen under simple random sampling probability in order to know their ecological habits and their predisposition for recycling, obtaining an estimate of the amount of materials used and discarded at the end of the academic semester; likewise, an interview was conducted with the university board to learn about the current management. Finally, a comprehensive waste management plan was proposed for the faculty which included the implementation of a recycling area in the academic department. Not only will this allow the proper segregation of solid waste but also promote a greener culture among the students, academic and administrative staff in order to show respect for the environment, improve the use of resources and reevaluate the waste, contributing to reduce the ecological footprint.